Learning the english simple present through fun activities, suchas flashcards, roulette, and bingo in the colegio particular a distancia Continental with students of tenth grade of basic - Plaza, Diana; Solis, Catalina
This tesina is about Learning the English Simple Present through Fun Activities, such as Flashcards, Roulette, and Bingo in the Colegio Particular a Distancia Continental with Students of Tenth Grade of Basic Education. We have chosen this theme because it is very important that these students learn English in a fun way because for them is difficult to learn English. There is a great time lapse between the time when they last studied and the time that they resumed their studies. Games develop the students? interest and creativity. Also, games allow us to practice one or more grammatical structures in a dynamic way. Besides, games are highly motivating and entertaining, and they help shy students to have more opportunity to express their opinions and feelings. Games help students to acquire new experiences in a foreign language. Nowadays, students are considered the main actors in the process of learning and the teacher is no longer considered the person with all the knowledge and all the right answers. Students are now able to participate in the classroom without being afraid to ask questions. We have classified didactic games or fun activities in three parts: flashcards, because they develop the visual memory of the students and facilitate the learning of the new vocabulary; roulette, because it is a fun way to practice grammatical categories through written expression; and bingo, because this game can be adapted to use in the classroom since it is an easy game; everybody can play it